Analisis Semiotika Makna Optimisme pada Video Klip Super-M “We-Do” - Kimberly Surjanto; Gregorius Genep Sukendro (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
Video clips are communication media that have meaning. To reveal a meaning, it is necessary to analyze using semiotic method. There are various types of semiotic methods, one of which is John Fiske's semiotic method. Using this method, the researcher wants to know the meaning of optimism described in the Super-M video clip with the title